Interpol wobec problemu tzw. zagranicznych bojowników terrorystycznych foreign terrorist fighters - Szumski, Adrian (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The challenges for present security include the problem of so-called foreign terrorist fighters. Threats concerned this issue are different, and they are a subject of interest of both countries and international organizations, including Interpol. The International Criminal Police Organization, being a worldwide entity, has broad possibilities of support of its member countries in fight against the above mentioned problem. This support concerns mainly help regarding an access to information, as well as coordination of actions being undertaken by law enforcement agencies.
Keywords: Interpol; terrorym; zagraniczni bojownicy terrorystyczni